Wind stress mediated variability of the Filchner Trough overflow, Weddell Sea - Daae, Kjersti; Darelius, Elin Maria K.; Fer, Ilker; Østerhus, Svein; Ryan, S. (Journal of Geophysical Research: Oceans, 2019)
The Filchner Trough (FT) is a key site for exchange of water masses between the Weddell Sea continental shelf and the deep ocean. Cold and dense Ice Shelf Water (ISW), a precursor for Antarctic Bottom Water, flows north along the FT and overflows the Filchner Sill. Although access of warm water to the Weddell Sea continental shelf is limited due to the presence of the Antarctic Slope Front, southward transport of warm water is facilitated through the FT. We use moored current meters from the Filchner Sill region to show that the monthly scale variability of the ISW overflow is connected to the variability of the alongslope wind stress upstream. Periods with significant correlation between the wind and ISW overflow are characterized by (I) wind directed along the continental slope, (II) high ISW overflow speed, and (III) high variability in the 16–64 day period band for wind and current. We propose that a recirculation of the slope current, associated with the Antarctic Slope Front, may occur in the FT during periods of strong wind forcing, and that such recirculation could explain the correlation between the wind stress and the ISW overflow. We further show that an increased wind stress along the continental slope leads to increased current speed within the slope current and the Antarctic Coastal Current, with possible implications for the on-shore heat transport. publishedVersion